The Analysis of the Effect of Bore Up Variation on Engine Performance - Widodo, Edi; Arbiantara, Difta; Iswanto (R.E.M. (Rekayasa Energi Manufaktur) Jurnal, 2023)
The purpose of this study was to determine the power, torque and fuel consumption of a Kawasaki Athlete motorcycle engine with a standard engine comparison, bore up of 0.50 mm, bore up of 1.00 mm, and bore up of 1.50 mm. The testing process uses a dynotes engine. With Pertamax fuel type. From the results of research that has been done, the performance has increased compared to the performance on a standard engine. The highest power is found in the 1.50 mm bore up variation of 10,2 Hp, the lowest power is found in the standard engine of 3,5 Hp. The highest torque is found in the 1.50 mm bore up variation of 10,31 N.m, the lowest torque is found in the standard engine of 3,40 N.m. For fuel consumption in each variation of the bore up has increased.